A high-throughput pipeline for DNA/RNA/small RNA purification from tissue samples for sequencing - Jing Xu; Pawan K Pandoh; Richard D Corbett; Duane Smailus; Reanne Bowlby; Denise Brooks; Helen McDonald; Simon Haile; Sundeep Chahal; Steve Bilobram; Karen L Mungall; Andrew J Mungall; et al. (BioTechniques)
High-throughput total nucleic acid (TNA) purification methods based on solid-phase reversible immobilization (SPRI) beads produce TNA suitable for both genomic and transcriptomic applications. Even so, small RNA species, including miRNA, bind weakly to SPRI beads under standard TNA purification conditions, necessitating a separate workflow using column-based methods that are difficult to automate. Here, an SPRI-based high-throughput TNA purification protocol that recovers DNA, RNA and small RNA, called GSC-modified RLT+ Aline bead-based protocol (GRAB-ALL), which incorporates modifications to enhance small RNA recovery is presented. GRAB-ALL was benchmarked against existing nucleic acid purification workflows and GRAB-ALL efficiently purifies TNA, including small RNA, for next-generation sequencing applications in a plate-based format suitable for automated high-throughput sample preparation.